1997
DOI: 10.1002/(sici)1096-8628(19970822)71:3<280::aid-ajmg6>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of familial congenital isolated anorectal malformations: Case report and review

Abstract: We report on a 3-generation family with 4 members affected with congenital low anorectal malformations. The vertical segregation of the anomalies and the occurrence of affected males and females support autosomal-dominant inheritance, which was suggested previously for this type of congenital anomaly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Concordance of ARM in monozygous twins has been reported [15] as well as 19 families with 2 or more sibs having isolated ARM. In some families, there were additional affected members from other generations, and all modes of inheritance (mendelian and multifactorial) have been put forward as the cause [16]. It is important to remember the dominantly inherited Currarino syndrome (ARM, presacral mass and hemisacral anomaly), where relatives may be asymptomatic or have nothing more than constipation despite having the homeobox gene (HLXB9) mutation on chromosome 7q36 [17].…”
Section: Discussionmentioning
confidence: 99%
“…Concordance of ARM in monozygous twins has been reported [15] as well as 19 families with 2 or more sibs having isolated ARM. In some families, there were additional affected members from other generations, and all modes of inheritance (mendelian and multifactorial) have been put forward as the cause [16]. It is important to remember the dominantly inherited Currarino syndrome (ARM, presacral mass and hemisacral anomaly), where relatives may be asymptomatic or have nothing more than constipation despite having the homeobox gene (HLXB9) mutation on chromosome 7q36 [17].…”
Section: Discussionmentioning
confidence: 99%
“…The isolated form may be associated with an autosomal dominant mode of inheritance, and from time to time, minor abnormalities such as ear malformation and thumb anomalies may be found [4]. Nevertheless, many forms of inheritance were proposed for familial ARM, dominant, recessive, x-linked, or even multifactorial [5][6][7][8], and only a few cases of hereditary isolated ARM are found in the literature [5,9]. Kubiak et al [10] made a review of the literature in 2005 to find a relation between twins/siblings and ARM.…”
Section: Discussionmentioning
confidence: 99%
“…For an alternative classification accentuating anatomy and functional outcome, see Pena [10]. From a genetic point of view, ARM can be divided into 2 main groups: ARM as part of a definite syndrome or in association with other anomalies, and isolated ARM [5]. Considerable effort has gone toward understanding the abnormal process that produces ARM, yet, to date, neither normal nor abnormal development of the hindgut and cloacal is fully understood [13].…”
Section: Discussionmentioning
confidence: 99%
“…Various forms of inheritance were proposed: autosomal dominant [1,3,5,6], autosomal recessive [4,7,9], and x-linked [4,8]. Schwoebel et al [3] suggested that if ARM occurs as an isolated malformation, possibly combined with minor additional malformations of the hands, feet and/or ears, it mostly follows the multifactorial mode of inheritance.…”
Section: Discussionmentioning
confidence: 99%